2015
DOI: 10.1109/tps.2015.2443856
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Investigation of a Cu—Cr Vacuum Arc

Abstract: Experiments on high-current arcs carried out in an ultrahigh vacuum chamber are presented in this paper. For contact separation the lower electrode is moved by a mechanicalpneumatic device simulating the conditions of a vacuum circuit breaker. The arc behavior of the Cu-Cr test electrodes after the electrode separation without application of external magnetic field is observed by a high-speed video camera. Besides the usual electrical measurements, the emission in the gap along the electrode axis is investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Figure 11 shows the experimental setup. A model vacuum switch [28] was used. The pressure in the vacuum chamber was typically about 10 −6 Pa. An AC current waveform at approximately 50 Hz was provided by a high-current generator.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 11 shows the experimental setup. A model vacuum switch [28] was used. The pressure in the vacuum chamber was typically about 10 −6 Pa. An AC current waveform at approximately 50 Hz was provided by a high-current generator.…”
Section: Methodsmentioning
confidence: 99%
“…The observation of lines with and without reabsorption dips (figure 3) prevents us from applying simple methods like the Boltzmann plot [22] or the Bartels methods [23], which have been developed for optically thin and thick plasmas, respectively. Instead, we apply the fitting procedure described in [7] for Cu-dominated arc, and applied successfully to other types of plasmas [18,24]. The basic idea of this method is to compute the emission spectra of the arc starting from assumed temperature and pressure profiles, and to optimize to the profiles that reproduce the best measured spectra [18].…”
Section: Temperature-dependence Of the Stark Shiftmentioning
confidence: 99%
“…In paper [4] the spatially resolved optical emission spectroscopy was used to study plasma parameters of high-current vacuum arcs between Cu-Cr contacts. It was found that the plasma layer in front of the anode is not in local thermal equilibrium (LTE).…”
Section: Introductionmentioning
confidence: 99%